The Creative Component Development in Educational Systems of the United Kingdom, the USA and Russia - Y. V. Sergeyeva (Russian State Vocational Pedagogical University, 2015)
To ensure the competitiveness and integration of the Russian educational system in the global educational environment it is necessary to study the experience of the leading countries faced by the problem of creativity fostering. The paper provides the comparative analysis of the content, approaches to and organizational forms of the creative faculty formation in educational systems of the United Kingdom, the United States and Russia. According to the author, the creative component is the inherent part of educational systems of the given countries, though its place in the system might be different. At the state level, the interest to creativity development is demonstrated by the statutory documents, official statements and legislative acts; their content reveals that both in Russia and the USA the interest to creativity fostering results from the state strategic policy, while in the UK the focus is on the economic prospects. The author mentions the centralized projects supported by the British government and aimed at stimulating creativity, though the participation of universities in the projects is optional. The didactic and methodological materials acquired by the author have the practical implications and can be used in teachers' training at various levels. The research materials were introduced at several Russian and International scientific conferences, discussed at seminars, round-table talks, and in the course of the International Creative Project performed by the students of Yekaterinburg and York in 2007-2013.